2015
DOI: 10.1152/jn.00688.2015
|View full text |Cite
|
Sign up to set email alerts
|

Predicting plasticity: acute context-dependent changes to vocal performance predict long-term age-dependent changes

Abstract: Understanding the factors that predict and guide variation in behavioral change can lend insight into mechanisms of motor plasticity and individual differences in behavior. The performance of adult birdsong changes with age in a manner that is similar to rapid context-dependent changes to song. To reveal mechanisms of vocal plasticity, we analyzed the degree to which variation in the direction and magnitude of age-dependent changes to Bengalese finch song could be predicted by variation in context-dependent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 111 publications
(127 reference statements)
1
39
0
Order By: Relevance
“…To analyse variation in song tempo between VD and LD song, we calculated the duration of the first motif of each song bout and analysed experimental variation in first motif durations using the same four-way factorial model as above (only first three bouts). Only the first motif in each bout was analysed for this comparison because motif durations change as bout length increases (e.g., Chi and Margoliash, 2001; Glaze and Troyer, 2006; James and Sakata, 2014; James and Sakata, 2015) and because bout lengths differed between VD and LD song (Figure 3; Table S2). There was no significant effect of any factor, including Condition, on song tempo (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyse variation in song tempo between VD and LD song, we calculated the duration of the first motif of each song bout and analysed experimental variation in first motif durations using the same four-way factorial model as above (only first three bouts). Only the first motif in each bout was analysed for this comparison because motif durations change as bout length increases (e.g., Chi and Margoliash, 2001; Glaze and Troyer, 2006; James and Sakata, 2014; James and Sakata, 2015) and because bout lengths differed between VD and LD song (Figure 3; Table S2). There was no significant effect of any factor, including Condition, on song tempo (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…In cases where few UD songs were produced between female presentations, UD songs produced in the 30 minutes before and after the testing period were used for analysis (16.2 ± 2.9 UD song bouts per male)(e.g. James and Sakata, 2015; Sakata et al, 2008; Toccalino et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting here that tutors and pupils were different ages when their songs were recorded and analyzed. This is potentially important because syllable sequencing changes over time in adult Bengalese finches 38,39 . For example, sequence variability at branch points decreases over time, due, in part, to a reduction in the number of branch point transitions.…”
Section: Discussionmentioning
confidence: 99%
“…The songs of individual Bengalese finches consist of a discrete, learned repertoire of syllables that are arranged both in highly stereotyped sequences ("motifs" or "chunks") and in sequences that vary from rendition to rendition ("branch points"; Fig. 1) 26,[33][34][35][36][37][38][39][40] . Previous studies have provided some insight into vocal sequence learning in Bengalese finches by comparing songs between tutors and pupils 41-43 ; for example, Yamashita et al (2008) analyzed the distribution of three-syllable sequences across two points in an individual's song development and found that the distribution approached that of his tutor's over time.…”
mentioning
confidence: 99%